Sosialisasi Penyuluhan Narkoba di Desa Sukadana - Sefin, Sefyandi; Safitri, Surya Lusiana; Satriawan, Ain Indra; Taiza, Tirta Ananta Raka; Sarwadi, Gagam (Insan Kreasi Media, 2023)
Abstract: In Indonesia, there is significant concern about the usage of drugs, particularly among the younger generation that forms the backbone of the construction sector of the nation. The public and government have adopted several steps, yet the issue is still getting worse. The method used in this socialization is the lecture and discussion method. This socialization aims to be able to develop the young generation with the ability and self-resilience against the influence of juvenile delinquency and avoid narcotics abuse. The results of the drug education socialization in Sukadana village, Bayan District, North Lombok Regency were very enthusiastically welcomed by local youth, this was proven by the large number of participants who attended this socialization and asked many questions. Apart from that, Kasatreskoba North Lombok describes the types of drugs starting from marijuana, crystal methamphetamine, and other psychotropic groups. It is hoped that with this drug education outreach, youth in Sukadana village can build a young generation that reflects goodness to other youth.